A Simulation and analysis of DSR Protocol in Mobile ad hoc Networks - Velagaleti, Sesha Bhargavi; Seetha, Dr.M.; Raju, Dr.S.Viswanadha (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
A MANET can be treated as a network in which the nodes have the capability of self-configuring among themselves. These nodes are connected by wireless links to form an distributed topology without the help of any pre-existing infrastructure. Each node in a MANET can itself act as a router on its own. To perform effective routing operation in MANETS , several routing protocols were proposed, addressing several issues in MANETS. In this paper ,we tried to study the operation of DSDV protocol ,which is a proactive protocol and analyse the results obtained by simualting the DSDV protocol using NS-2 Simulator.